Clinical advances and challenges of anti-angiogenic targeted therapy in gastric cancer - Wu, Zhongyue; Ni, Jiaojiao; Xu, Qi (Frontiers in Oncology, 2025)
Gastric cancer (GC) is a malignant neoplasm with one of the highest incidence and mortality rates. However, therapeutic options remain limited for advanced disease. Angiogenesis, a fundamental process in tumor progression, has emerged as a key therapeutic target. To comprehensively evaluate the clinical advancements of anti-angiogenic targeted drugs, this review conducted a systematic search and collation of pertinent literature, While, only ramucirumab achieved regulatory approval for second-line therapy, emerging agents including apatinib and fruquintinib demonstrate significant clinical benefits, particularly in combination with immunotherapy. The review also classifies and summarizes biomarkers with potential predictive value for treatment response, and discusses the current major challenges and potential optimization strategies. This analysis identifies significant gaps in predictive biomarkers and emphasizes that patient stratification and rational combination strategies are essential for optimizing therapeutic outcomes.